Sistem Pakar untuk Mendeteksi Gejala Awal Penyakit Apendisitis dengan Metode Case Based Reasoning (CBR) Berbasis Mobile Android - Nugroho, Catur; Wiranata, Ade Davy; Aldisa, Rima Tamara (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2022)
Appendicitis is caused by inflammation of the intestines (appenditis). The patient will feel pain in the lower right abdomen. This study explores this with several references, by designing an expert system an application is produced that is used to detect appendicitis. This process can help detect early symptoms starting from the user answering questions in the form of symptoms suffered by the user. The research applies the Case Base Reasoning method in the expert system by detecting the early symptoms of appendicitis using this android-based device. The research aims to add experience to users in finding out the disease they feel by entering the initial symptoms and providing solutions or it can be without consulting the nearest hospital or clinic. The results of the research. This android-based appendicitis expert system aims to help diagnose Appendicitis Inflammatory Disease for children under five and adults based on Android Mobile, and the Appendicitis Disease Diagnosis Expert System that was built to provide information easily starting from understanding, dangers, causal factors, symptoms of the disease and solution only by consulting the system and objectives can help provide a good solution.